Opportunities for Grade 11 students to learn Euclidean geometry in some South African schools - Ogbonnaya, Ugorji I.; Bogoshi, Maria M. (African Perspectives of Research in Teaching & Learning (APORTAL), 2024)
This research paper investigated the opportunities for Grade 11 students to learn Euclidean geometry in some South African schools. The study aimed to examine the Euclidean geometry curriculum covered in these schools and the instructional time used in teaching this content. The research was conducted within a single education district in the Gauteng province and involved six secondary schools. Data collection relied on teaching and learning materials. Results revealed that the depth of content coverage varied across schools, with two schools notably lacking in comprehensive instruction. Furthermore, concerning instructional time, three schools fell short of the recommended duration for teaching the content. These findings suggest that students may not have received adequate learning opportunities on the topic. The paper discussed the implications of these findings and proposed recommendations for addressing the observed shortcomings.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 2, Volume 8, 2024
Keywords: Content coverage; Euclidean geometry; Instructional time; Opportunity to learn; Time on task; Geometry; Generalized spaces; Mathematics -- Study and teaching (Secondary) -- South Africa -- Gauteng; Geometry -- Study and teaching (Secondary)